Enhancing and utilizing the Production of Keratinase Enzymes from Bacillus amyloliquefaciens for the Recycling of Feather Waste - Hillo, Nassir; Noor M. Ahmed Al-Amery (University of Thi-Qar Journal of Science, 2025)
The use of the microbial keratinase enzyme to remediate keratinous waste is an attractive approach in green processing and biotechnology, aiming to eliminate waste accumulation in the environment and recycle it into economical or nutritional products. This study aims to enhance the environmental and nutritional conditions of the growth medium for a keratinolytic bacterium isolated from the soil of a poultry farm in Basrah Province, Iraq, to increase its keratinase production. Subsequently, the keratinase will be used to convert feathers into a poultry feed supplement (feather meal).  In the present study, the bacterial isolate was identified as Bacillus amyloliquefaciens strain 19E2. The optimal conditions for keratinase enzyme production were determined by evaluating various factors, including temperature, pH, carbon sources, nitrogen sources, and inoculum size. The keratinase activity before optimizing the environmental and nutritional conditions was measured at 42.1 U, after applying the best at 37°C, pH 8, tryptone as the preferred nitrogen source, glucose as the preferred carbon source, and an inoculum size of 1 ml during a 48-hour incubation period, the keratinase activity increased to 129.3 U. This Bacillus amyloliquefaciens strain 19E2 was then utilized to convert 25 g of feathers into 8 g of feather meal, which was tested by FTIR and found to be a rich source of amino acids and short peptides for use as a nutritional supplement.